Veiksmažodžių tyrinėjimų keliai - Jakulis, Erdvilas (Baltistica, 2006)
WAYS OF VERB RESEARCHThis article is an answer to the review by M. Villanueva Svensson. It shows, that certain arguments by the reviewer regarding the origin of tekėti, teka verb type, the motives and the method of its formation are debatable. Therefore the author maintains his opinion that:1. Tekėti, teka type verbs are an exclusive innovation of the East Balts. There was no such type in the Old Prussian language, whereas in the Slavic languages the processes of type re-formation took place for other reasons and in a different way, therefore similar verbs or even verbs with similar structure should be considered as independent formations instead of common innovations by Slavs and Balts.2. The oldest verbs of this East Baltic structural type were formed from root-verbs. It was not the infinitive, but the preterit where the changes took place: attachment of one more stem final -ā to the stem final of the preterit -ē formed *-ēi̯ā. The same stem final -ē- was generalised for the infinitive(*tekti — *tekē+ti* = *tekēti).
Keywords: lietuvių kalba; veiksmažodis